2023
DOI: 10.7759/cureus.34601
|View full text |Cite
|
Sign up to set email alerts
|

Post Radical Prostatectomy Erectile Dysfunction. A Single Centre Experience

Abstract: Introduction: This study aims to determine the effects of radical retropubic prostatectomy on post-operative erectile function.Materials & Methods: A total of 50 patients were included in this study, diagnosed with localized prostate cancer, and underwent nerve-sparing radical retropubic prostatectomy. All patients completed the International Index of Erectile Function (IIEF-5) questionnaire pre-operatively and on the third, sixth, and twelfth post-operative month and completed a self-reporting of their satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…This lends strength to the findings for scores 7 and 9 as well as the hypothesis that higher Gleason scores imply a higher ED index in the prognosis, as expected based on the literature. 5 Smoking was not significantly correlated with any of variable of PDE5 inhibitor use. Thus, there were no relevant statistical differences among smokers, ex-smokers and non-smokers for ED following RP in this study.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This lends strength to the findings for scores 7 and 9 as well as the hypothesis that higher Gleason scores imply a higher ED index in the prognosis, as expected based on the literature. 5 Smoking was not significantly correlated with any of variable of PDE5 inhibitor use. Thus, there were no relevant statistical differences among smokers, ex-smokers and non-smokers for ED following RP in this study.…”
Section: Discussionmentioning
confidence: 86%
“…However, the rate was close to that found in the recent literature, which reported the prevalence of ED following RP to be 82.6%, without describing the time of the postoperative period or severity of ED 15 . Rates of severe dysfunction six months after the procedure were 74% and 57.3% in two studies, 5,11 whereas other studies reported the prevalence to be 76 to 87% at six months after the procedure, depending on the preservation of local nerves. 2 The daily use of tadalafil in the first three months following RP was significantly correlated with the Gleason score (p = 0.001).…”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations